It's Not Easy Being Big! - Dr. Seuss; Stephanie St. Pierre (New York Random House, 1998)
In this oh-so-easy-to-read introduction to spatial relationships, Big Bird and Small Bird discover that sometimes it's not easy being big and sometimes it's not easy being small. But sometimes it is.
Keywords: Read Aloud -- Read Aloud